Overactive bladder following surgical intervention for benign prostatic hyperplasia: treatment outcomes in routine clinical practice - D. A. Bogdanov; A. G. Yusufov; R. I. Guspanov; S. V. Kotov (Вестник урологии, 2025)
Introduction. Various surgical methods for the treatment of benign prostatic hyperplasia (BPH) effectively alleviate voiding symptoms and improve urinary flow quality. However, patient satisfaction often decreases due to the persistence of storage symptoms following surgical intervention.Objective. To determine the prevalence of persistent storage symptoms and overactive bladder (OAB), optimal approaches to the treatment of symptoms after surgical treatment of BPH in clinical practice.Materials & methods. The study included 94 patients aged 53 – 79 years who underwent surgery for BPH, with persistent storage symptoms in 1 – 3 months after surgery (IPSS-storage score ≥ 3). The patients underwent urodynamic examination. In the case of persistent symptoms without confirmed OAB, behavioral therapy was performed (group 1). In case of detrusor overactivity («dry» OAB), patients were prescribed medication solifenacin 5 mg daily (group 2), in case of terminal detrusor overactivity, urgent urinary incontinence («wet» OAB), combination therapy solifenacin 5 mg + mirabegron 50 mg (group 3) was prescribed.Results. Patient characteristics in the preoperative period showed no statistically significant differences between groups regarding age, urodynamic parameters, and lower urinary tract symptoms (LUTS) as assessed by the IPSS questionnaire. At the initiation of therapy, the median storage symptom scores were 4, 8, and 9 points in groups 1, 2, and 3, respectively. Both the behavioral and pharmacological therapy groups demonstrated a statistically significant reduction in the severity of storage symptoms over time (p < 0.001). After 12 weeks, the median storage symptom scores were 3 points in group 1, 4 points in group 2, and 6 points in group 3. Urgent incontinence was eliminated in group 3 after treatment. By 12 months after surgical treatment and drug therapy, the irritative symptoms and the number of nocturia episodes approach equal values in all groups (p > 0.05). Patients from the drug therapy groups showed high adherence to therapy, among them there were no significant side effects requiring discontinuation of therapy.Conclusion. The use of pharmacological therapy with M-cholinergic antagonists and/or β3-adrenoceptor agonists in the postoperative period in patients with confirmed detrusor overactivity contributes to a reduction in urgency symptoms and enhances patient treatment satisfaction. In the absence of detrusor overactivity or with an IPSS storage score ≤ 6, behavioral therapy represents a viable alternative to pharmacological treatment.